Application of e-Leaflet-Assisted Jigsaw-Type Cooperative Learning Model to Improve Communication Skills of Class X Students on Ecosystem Materials - Ramadhanti, Ramadhanti; Maknun, Djohar; Ekanara, Bambang; Subagyo, Subagyo (Annpublisher, 2025)
Background. To maximize both, a learning model is needed that can combine them, such as the Jigsaw learning model. Aims. The objectives of this research are to: (1) identify the application of Jigsaw learning model assisted by e-Leaflet to communication skills; (2) analyze the differences in communication skills in students who use e-leaflet assisted learning model and those who use Leaflet assisted learning model; (3) analyze student responses during the implementation of Jigsaw learning model assisted by e-Leaflet. Methods. This study used a quasi-experimental method with a Nonrandomized Control Group Pretest-Posttest Design involving two classes at SMAN 1 Dukupuntang. The sample was selected through purposive sampling. Data collection was done through observation, e-Leaflet product assessment, communication skills test, questionnaire, and interview. Result. The results showed that: (1) the activity of students in the experimental class was excellent, and their communication skills were higher than those in the control class; (2) based on the analysis of test scores, there was a significant difference in students' communication skills; and (3) students' responses to the Jigsaw learning model assisted by e-Leaflet were high in terms of the effectiveness of e-Leaflet, involvement in the Jigsaw model and communication skills. Conclusion. This study confirms that the Jigsaw learning model, assisted by e-Leaflet, can improve students' activity and communication skills, although its application still presents obstacles. Implementation. The application of the Jigsaw model requires more attention to student characteristics and the provision of adequate facilities and technology to ensure the learning process runs optimally